2020
DOI: 10.1186/s12889-020-09287-z
|View full text |Cite
|
Sign up to set email alerts
|

Is sleep duration associated with overweight/obesity in Indigenous Australian adults?

Abstract: Background: Associations between high BMI and sleep duration and chronic illness are recognised. Short sleep is an accepted predictor of high BMI for children, including Indigenous Australian children. Short sleep has also been associated with high BMI in Australian adults, although not specifically in Indigenous Australian adults. This study aims to determine whether the relationship between sleep duration and BMI observed in non-Indigenous adults holds for Indigenous adults. Methods: Data collected from 5204… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(28 citation statements)
references
References 44 publications
3
22
0
Order By: Relevance
“…Consistent with previous reports [ 48 ], and as we have previously described [ 21 ], increased BMI was independently associated with short sleep duration of less than 7 hours, but not with long sleep of greater than 9 hours. Notably, after accounting for possible confounding influences, Indigenous status was a significant predictor of BMI.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Consistent with previous reports [ 48 ], and as we have previously described [ 21 ], increased BMI was independently associated with short sleep duration of less than 7 hours, but not with long sleep of greater than 9 hours. Notably, after accounting for possible confounding influences, Indigenous status was a significant predictor of BMI.…”
Section: Discussionsupporting
confidence: 92%
“…This study used the same dataset and followed on from our previous report [ 21 ]. In short, the dataset from participants in the Australian Health Survey (AHS) and the complementary Australian Aboriginal and Torres Strait Islander Health Survey (AATSIHS) was provided by the Australian Bureau of Statistics (ABS).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, those with negative changes in sleep quality reported more weight gain than those with positive changes [ 4 ]. With regards to the relationship of sleep duration with weigh status in Australians, it was found that the odds of overweight/obesity were the greatest for those who slept <6 h, and the risk of overweight/obesity decreased for those with sleep >7 h [ 13 ]. Moreover, compared with recommended sleep time (i.e., ≥7 to ≤9 h) in U.S., American black women who were very short sleepers (≤6 h) and long sleepers (>9 h) had a significantly greater body mass index (BMI) [ 14 ].…”
Section: Introductionmentioning
confidence: 99%